2018
DOI: 10.3389/fendo.2018.00321
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism in Children With Growth Hormone Deficiency

Abstract: BackgroundThe growth hormone (GH)/insulin-like growth factor 1 (IGF-1) axis has a fundamental impact on glucose metabolism. Therefore, both untreated GH deficiency (GHD) and GH treatment (GHT) may be associated with some metabolic alterations, although the abnormalities of glucose metabolism have been investigated by relatively few studies as main outcomes.AimThe present review summarizes the available data on glucose metabolism in children with GHD, providing an overview of the current state of the art in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…Several other studies have investigated the effects of rhGH therapy on glucose metabolism in children (17,18,19,20,21,22). Nevertheless, as highlighted in a recent systematic review (8), only in relatively few studies glucose metabolism abnormalities were the main outcome. The use of different methods to study glucose metabolism and the heterogeneity of the populations evaluated precluded the possibility of obtaining strong evidence of possible glycemic alterations caused by rhGH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have investigated the effects of rhGH therapy on glucose metabolism in children (17,18,19,20,21,22). Nevertheless, as highlighted in a recent systematic review (8), only in relatively few studies glucose metabolism abnormalities were the main outcome. The use of different methods to study glucose metabolism and the heterogeneity of the populations evaluated precluded the possibility of obtaining strong evidence of possible glycemic alterations caused by rhGH.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a variety of different parameters and indices have been used to study the influence of GH treatment on glucose and insulin homeostasis (8). Biomarkers such as glycated hemoglobin A1c (HbA1c) and indices of glucose tolerance are now widely employed in the diagnosis and monitoring of patients with glucose abnormalities, but only one report explored their potential application in the field of rhGH therapy over a one year follow-up period (9).…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published review, the authors found that in the majority of studies, GH treatment in children resulted in a subtle form of insulin resistance, though FPG and glycated haemoglobin (HbA1c) mostly remained in the normal range. 43 New onset T2DM rarely occurs during GH treatment in children with GH deficiency or even with idiopathic short stature. 44 Those with Turner syndrome and children who are small for gestational age, have a higher lifetime chance of developing T2DM compared with the background population, but GH therapy in such children does not alter the incidence of T2DM in short term.…”
Section: Alteration In Glucose Metabolism With Drugs Used For the Trementioning
confidence: 99%
“…Several other studies have investigated the effects of rhGH therapy on glucose metabolism in children (17)(18)(19)(20)(21)(22). Nevertheless, as highlighted in a recent systematic review (8), only in relatively few studies glucose metabolism abnormalities were the main outcome. The use of different methods to study glucose metabolism and the heterogeneity of the populations evaluated, precluded the possibility to obtain strong evidence on possible glycemic alterations caused by rhGH.…”
Section: Evaluation Of Glucose Metabolismmentioning
confidence: 99%
“…Concerning insulin sensitivity, GH treatment leads to a compensatory increase in insulin secretion before the appearance of overt glucose abnormalities (1), so decreased insulin sensitivity may be detected even without changes in glucose tolerance (7). In recent years, a variety of different parameters and indexes have been used to study the influence of GH treatment on glucose and insulin homeostasis (8). Biomarkers as glycated hemoglobin (HbA1C) and indexes of glucose tolerance are now widely employed in the diagnosis and monitoring of patients with glucose abnormalities, but only one report explored their potential application in the field of rhGH therapy over a short follow-up period (9).…”
Section: Introductionmentioning
confidence: 99%